Management Accounting Information’s Effect on E-Clinic Usage through Performance as an Intervening Variable - Suheny, Eny; Holilah, Holilah; Maelani, Puspita (Interdisciplinary Social Studies, 2022)
This research is motivated by the rapid development of IT-based information and technology and is increasingly widely known by the wider community, starting from information media which was initially only used on paper media, now switching to computerized media. Almost all companies, organizations, institutions, hospitals and government agencies require fast, precise and accurate data and information management in improving their performance, one of which is a clinic in which there is also information management. The purpose of this study is to analyze and examine whether there is an influence between management accounting information on the use of e-clinics and performance measurement as an intervening variable. The research method uses quantitative methods, using SPPS as a data processing tool and Sobel test to test the intervening variables. The results of this study are there is an influence between management accounting information on the use of e-clinics, there is no effect between management accounting information on performance measurement, there is an influence between performance measurements on the use of e-clinics, there is no effect between management accounting information systems on the use of e-clinics -clinic with performance measurement as an intervening variable.